Role of the Lipid Membrane and Membrane Proteins in Tau Pathology - Bok, Eugene; Leem, Eunju; Lee, Bo-Ram; Lee, Ji Min; Yoo, Chang Jae; Lee, Eun Mi; Kim, Jaekwang (Frontiers in Cell and Developmental Biology, 2021)
Abnormal accumulation of misfolded tau aggregates is a pathological hallmark of various tauopathies including Alzheimer’s disease (AD). Although tau is a cytosolic microtubule-associated protein enriched in neurons, it is also found in extracellular milieu, such as interstitial fluid, cerebrospinal fluid, and blood. Accumulating evidence showed that pathological tau spreads along anatomically connected areas in the brain through intercellular transmission and templated misfolding, thereby inducing neurodegeneration and cognitive dysfunction. In line with this, the spatiotemporal spreading of tau pathology is closely correlated with cognitive decline in AD patients. Although the secretion and uptake of tau involve multiple different pathways depending on tau species and cell types, a growing body of evidence suggested that tau is largely secreted in a vesicle-free forms. In this regard, the interaction of vesicle-free tau with membrane is gaining growing attention due to its importance for both of tau secretion and uptake as well as aggregation. Here, we review the recent literature on the mechanisms of the tau-membrane interaction and highlights the roles of lipids and proteins at the membrane in the tau-membrane interaction as well as tau aggregation.